Biomimetic Targeted Co‐Delivery System Engineered from Genomic Insights for Precision Treatment of Osteosarcoma - Tianqi Luo; Zhijin Fan; Anyu Zeng; Anqi Wang; Yuanwei Pan; Yanyang Xu; Hongmin Chen; Weiqing Chen; Dingmeng Nie; Jiaming Lin; Anfei Huang; Ming Gong; et al. (Advanced Science)
Abstract The high heterogeneity and severe side effects of chemotherapy are major factors contributing to the failure of osteosarcoma treatment. Herein, a comprehensive genomic analysis is conducted, and identified two prominent characteristics of osteosarcoma: significant cyclin‐dependent kinases 4 (CDK4) amplification and homologous recombination repair deficiency. Based on these findings, a co‐delivery system loaded with CDK4/6 inhibitors and poly ADP‐ribose polymerase (PARP) inhibitors is designed. By employing metal–organic frameworks (MOFs) as carriers, issue of drug insolubility is effectively addressed, while also enabling controlled release in response to the tumor microenvironment. To enhance targeting capability and biocompatibility, the MOFs are further coated with a bio‐membrane targeting B7H3. This targeted biomimetic co‐delivery system possesses several key features: 1) it can precisely target osteosarcoma with high B7H3 expression; 2) the combination of CDK4/6 inhibitors and PARP inhibitors exhibits synergistic effects, significantly impairing tumor's DNA repair capacity; and 3) the system has the potential for combination with photodynamic therapy, amplifying DNA repair defects to maximize tumor cell eradication. Furthermore, it is observed that this co‐delivery system can activate immune microenvironment, increasing CD8+ T cell infiltration and converting osteosarcoma from an immune‐cold to an immune‐hot tumor. In summary, the co‐delivery system is an effective therapeutic strategy and holds promise as a novel approach for osteosarcoma treatment.